Characteristics of book distribution administrative-legal regulation in the Russian province at the second half of the XIX century - M. A. Shitskova (Библиосфера, 2016)
The central component of social determination in developing book distribution becomes the administrative-legal regulation of this activity at the second half of the XIX century. It is determined that the external context of book distribution development in the Russian provinces in late ХIХ century was formed, on the one hand, by the priorities and objectives of the book business state regulation, on the other hand, by features and understanding of their implementation of the provincial administrative authorities. The study objective is historical reconstruction of the state regulation of the provincial book distribution in the Russian province in the second half of the ХIХ century. The legal terms of book distribution was both the all-Russian laws on censorship and printing and confidential circulars of the Ministry of Internal Affairs. The circulars instructed the governors to issue permits on the book trade mainly in major cities of the province, where it was ensured strict police surveillance over book-selling activity. The secret orders of the Ministry of Internal Affairs did not contributed to the book trade development in provinces, moreover, the implementation of legislative norms depended on the arbitrariness of local officials, who sought to suppress private initiatives and not to permit bookselling business in regions. A guarantor of law implementation in the province was the governor, and the direct supervision of book-trade activities was carried out by the local police department. Thus, referring to archival documents of the central and regional archives, the author presents a conclusion about the dual nature of legal regulation of book business as a whole, and bookselling activities in particular. The legislation concerning press formed the national context of reading development, its practical application infused their territorial features.